Compressible (Fanno Flow) of Air in a Pipe - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2014)
Fanno Flow calculations for adiabatic, compressible air flow in a pipe are very time-consuming as they require multiple levels of difficult calculations using tables and iterative solutions. This Excel workbook streamlines these calculations by automating the iterative calculation of the friction factor and the overlaying iterative solution of the Fanno Flow equation. Incompressible flow calculations are made first to check whether the incompressible flow calculations are adequate. If compressible flow calculations are required, worksheets using a Fanno Flow calculator are provided to calculate the frictional pressure drop, flow rate, or required diameter based on input of the other pipe flow parameters and inlet air temperature and pressure.